Resepsi Fungsional QS Ali-Imran: 191 Tradisi Bratit Semin dalam Meminta Hujan Masyarakat Semurup, Kab. Kerinci: Functional Reception of QS Ali-Imran: 191 Bratit Semin Tradition in Asking for Rain for the Semurup Community, Kerinci - Suhada, Farhan (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
This study aims to explore the functional reception of Surah Ali Imran: 191 understood by the people of Semurup, Kerinci Regency as a prayer for rain in the Bratit Semin tradition. Using the Hans Robert Jauss reception theory approach that emphasizes the response of readers or connoisseurs of literary works to a text. This form of reception is oriented towards understanding the meaning or form of religious rituals. Surah Ali Imran 191 in the early days of Islam was understood as part of the routine of a Muslim's faith, while in modern times began to understand the gift of reason given by God as a way to think. While al-Ghazali understands the meaning of this verse as a way to get closer to Allah through dhikr and prayer in being a solution to every problem faced. By using the descriptive-analytical method, which describes the phenomena that occur with existing data in the form of writing or interviews and then analyzing using Hans Robert Jauss's literary reception theory approach, this article concludes that Surah Ali Imran 191 can be understood as a means of asking for rain when there is a long drought, this is also influenced by the way Islam entered the Kerinci community when it was presented by tarekat scholars who had learned directly from Arabia when carrying out the Hajj.